Effectiveness of Spiritual Intelligence in Resilience and Responsibility of Students - Ali Javadi Nejad; Alireza Heidari; Farah Naderi; Saeed Bakhtiyar Pour; Fariba Haffezi (Shiraz University of Medical Sciences, 2019)
Background: Spiritual intelligence is one of the important and influential variables in many psychological characteristics including resilience and responsibility. Objectives: Based thereon, the present study was conducted with the objective of determining the effectiveness of spiritual intelligence training in responsibility and resilience of secondary high school students in the city of Baghmalek. Methods: The present study was a semi-experimental study with pretest-posttest design and experimental/control groups. The research population included all secondary high school students from Baghmalek city during 2017 - 2018. Finally, 60 students were selected by the multistage cluster sampling method and randomly assigned to experimental and control groups. Data collection was done using the Connor-Davidson resilience scale (CD-RISC) and Kordlou's responsibility questionnaire. The experimental group participated in eight 90-min sessions for spiritual intelligence instruction while the control group was placed in a waiting list and did not receive any instructions. After the termination of the sessions, both of the groups were subjected to posttest. Results: The results indicated that there was a linear significant relationship between the pretest and posttest scores of resilience (F = 56.32, P < 0.001) and the pretest and posttest scores of responsibility (F = 12.98, P = 0.004) in the experimental and control groups. The results of univariate analysis for resilience (F = 15.55, P < 0.001) and responsibility (F = 7.14, P = 0.016) as dependent variables were found significant. Thus, spiritual intelligence instruction increased resilience and responsibility in students. Conclusions: Spiritual intelligence training could be an appropriate interventional method for enhancing the students' responsibility and resilience considering the society's need for committed and flexible students who can resist problems and challenges.